Antifungal activity of volatile organic compounds from essential oils against the postharvest pathogens Botrytis cinerea, Monilinia fructicola, Monilinia fructigena, and Monilinia laxa - Álvarez-García, Samuel; Moumni, Marwa; Romanazzi, Gianfranco (Frontiers in Plant Science, 2023)
Gray mold and brown rot, caused respectively by Botrytis cinerea and Monilinia spp., are fungal diseases responsible for significant losses during the storage of fruit and vegetables. Nowadays, the control of postharvest diseases is shifting towards more sustainable strategies, including the use of plant secondary metabolites. In this study, the antifungal activity of Origanum vulgare, Thymus vulgaris, Thymus serpyllum, Melaleuca alternifolia, Lavandula officinalis, Lavandula hybrida, Citrus bergamia, Rosmarinus officinalis, Cinnamomum zeylanicum essential oils (EOs) in vapor phase was tested in vitro against B. cinerea, Monilinia fructicola, Monilinia fructigena, and Monilinia laxa. For the experiments, a protocol using a volatile organic compounds (VOC) chamber was designed. Results indicate a dose-dependent inhibitory activity of all the tested EOs, with O. vulgare, T. vulgaris, and T. serpyllum being the most active ones, with minimum inhibitory concentrations (MIC) of 22.73, 45.45, and 22.73 µl/L, respectively, against B. cinerea and a range between 5.64 and 22.73 µl/L against the three Monilinia spp. Overall, B. cinerea presented lower sensitivity to vapor-phase EOs than any of the Monilinia strains, except for the C. zeylanicum EO, which consistently showed higher inhibition against B. cinerea. Among the three Monilinia spp., M. fructicola was the least sensitive, while M. fructigena was the most sensitive. The use of VOC chambers proved to be a reliable protocol for the assessment of antimicrobial activities of EOs. These results suggest that the VOC emitted by the tested EOs are effective towards important decay-causing fungi, and that they could be used for the control of gray mold and brown rot in in vivo trials.